Problems and solutions on solid state physics, relativity and miscellaneous topics (World Scientific, 1995)
This book consists 165 problems. Both special and general relativity problems are included, although some other special relativity problems have been solved elsewhere, particularly in the volumes on Mechanics and on Electromagnetism